Potentially lethal mouth diseases: pemphigus - Ficarra, Giuseppe (Henry Stewart Talks, 2017)
Epidemiology, Oral and skin clinical features, Pathogenesis, Diagnosis, Role of direct and indirect immunofluorescence, Therapeutic strategy, Paraneoplastic pemphigus